ചെഗുവേര റീഡർ (Che Guevara reader) - ഡ്യൂഷ്മൻ,ഡേവിഡ് (Deutschmann,David); രാഘവൻ വേങ്ങാട് (Raghavan Vengad),Tr (Chintha Publications, 2006)
Che Guevara Reader edited by David Deutschmann is the bestselling, most comprehensive selection of Che Guevara’s writings, letters and speeches. This volume covers Che’s writings on the Cuban revolutionary war, the first years of the revolution in Cuba and his vision for Latin America and the Third World. It includes such classic essays as 'Cubayile Socialisavum Manushyanum' and his call to create "Two, Three, Many Vietnams."